Can Bio-Based Thermoset Polymers Replace Petrochemical Based Counterparts? - Adekunle, Kayode Feyisetan (Journal of Research Updates in Polymer Science, 2013)
Specific answers are required for purpose of better communication with many researchers, manufacturers, and users of polymer worldwide. This paper posted so many questions about the research activities on bio-based/ renewable thermoset polymers as against petrochemical based thermoset polymers. Quite a few answers were given but the remaining unanswered questions will surely be required in order to better understand the results achieved in this research area.